(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
This study examined land use patterns and efficiency of crop production among farmers in Ogun State, Nigeria. A multistage sampling procedure was used to select respondents for the study. Data were collected using structured questionnaire and interview method. A total of 128 respondents were used for the conduct of the analysis. The analytical tools employed were descriptive statistics such as frequencies percentages, measures of dispersion and measures of central tendency, budgetary analysis as well as the Stochastic Frontier Production Function (SPF). Results of the analysis revealed that majority of the farmers were male, married, highly experienced and formally educated. The predominant cropping pattern was mixed cropping and continuous farming was mostly practiced. Budgetary analysis showed that the farming was profitable. However, with respect to cropping pattern and farming system, sole cropping and crop rotation were most profitable. Seed, labour and herbicide had significant effect on the technical efficiency of the farmers. Farming experience and household size were seen to contribute to the inefficiency level of the respondents. The respondents had a mean technical efficiency of 0.6749, indicating that in order for them to operate on the frontier, they have to overcome an inefficiency level of 32.51%. Laws binding land acquisition should be made flexible, so as to encourage farmers to expand their production and to reduce pressure on lands brought about by mixed farming and continuous cropping systems.